BILA BUKAN ASAP ROKOK (Biji Labu Kuning (Cucurbita moschata duchesne) dan Asap Rokok - Regina Desyca Sarmitha Dewi (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2019)
Some components of cigarette smoke are gases, such as CO, CO2, HCN, and NOx which are the potential to cause free radicals. PAH contained in Cigarette smoke can cause testicular atrophy,inhibits spermatogenesis, and damage the morphology of spermatozoa, moreover nicotine exposure causes a decrease in testosterone levels through the mechanism of inhibition of Leydig cell function where functions is a testosterone hormone secretor. Pumpkin seeds has contain alkaloid compounds,saponins, kukurbitasin, lecithin, resins, stearin, phytosterol compounds, phenolic, fatty acids, squalen,tyrosol, vanylic acid, vanillin, luteolin and sinapat acids, vitamins (including vitamin β-carotene, vitaminA, vitamin B2, a-tocopherol, vitamin C and vitamin E). Vitamin C is a watersoluble vitamin that canprotect spermatozoa from damage by oxidative stress by neutralizing hydroxyl, superoxide and hydrogen peroxide radicals and prevent agglutination of spermatozoa. Vitamin E can reduce the levels of malondialdehyde in spermatozoa, increase spermatozoa motility and play a role in reducing DNAfragmentation of spermatozoa. The research has become the basis of writing health articles aimed at new contributions to science.